Simplify the following expression 7a + 5b - 2a + b
2 answers:
5a+6b would be the simplified answer
Answer:
<h2><u><em>
5a + 6b</em></u></h2>
Step-by-step explanation:
Simplify the following expression:
Simplify the following expression:
7a + 5b - 2a + b =
5a + 6b
You might be interested in
Answer:
2,406.16452 cm
Step-by-step explanation:
(1/3)*(17.2*17.2)*24.4
98.61333*24.4
2,406.16452cm
Answer:
x=4
Step-by-step explanation:
all you need to do is the 3rd root of 64
which is 4.
Answer:
-1
Step-by-step explanation:
we would use the slope formula which is y2-y2/x2-x1
so 3-4/5-4= -1
These are vertical angles, meaning they're always the same length.
![3x = x + 28](https://tex.z-dn.net/?f=3x%20%3D%20x%20%2B%2028)
![2x = 28](https://tex.z-dn.net/?f=2x%20%3D%2028)
![x = 14](https://tex.z-dn.net/?f=x%20%3D%2014)
116 degrees. It’s simple.
56 is what the low was, but the high was 60 more.
Therefore,
56+60=116